Search for CP violation in K0→3π0 decays - Lai, A; Marras, D; Batley, JR; Dosanjh, R; Gershon, T; Kalmus, G; Lazzeroni, C; Munday, D; Olaiya, E; Parker, M; White, T; Wotton, SA; et al. (2005)
Using data taken during the year 2000 with the NA48 detector at the CERN SPS, a search for the CP violating decay KS→3π0 has been performed. From a fit to the lifetime distribution of about 4.9 million reconstructed K0/K̄0→3π0 decays, the CP violating amplitude η000=A(KS→3π0)/ A(KL→3π0) has been found to be Re(η000)=-0.002±0.011±0.015 and Im(η000)=-0.003±0. 013±0.017. This corresponds to an upper limit on the branching fraction of Br(KS→3π0)<7.4×10-7 at 90% confidence level. The result is used to improve knowledge of Re(ε) and the CPT violating quantity Im(δ) via the Bell-Steinberger relation. © 2005 Elsevier B.V. All rights reserved.